Morfología del esporófito y el gametófito de Asplenium dareoides (Aspleniaceae, Pteridophyta) - Lavalle, María del Carmen (2007)
Sporophyte morphology of Asplenium dareoides was reviewed, and development and morphology of its gamethophytes were studied for the first time from spore culture on mineral agar. Spores germinated 10 days after sown, and cultures reached a low percentage of germination (1 to 5%). Filamentous phase was initiated at 15 days. Gametophytes followed the Aspidium type of development, which leads to a hairy adult state, with cylindrical, marginal and superficial hairs. The morphological study of the sporophyte was based on foliar architecture, indument, epidermal patterns of pinnulae and indusium, spore size (mean values between 28.9 and 39.7 μm) and spore morphology. Gametic chromosome number found was n = 72. Morphological and palynological characters of A. dareoides do not support the close relationship with A. flabellifolium, recently suggested from molecular data.